A single-subject comparison of functional outcomes between lower limb salvage vs. transtibial amputation through sequential participation in a fall-prevention program. Issue 6 (7th December 2022) - Acasio, Julian C.; Tullos, Meghan L.; Mahon, Caitlin E.; Khatri, Binni R.; Kaufman, Kenton R.; Dearth, Christopher L.; Hendershot, Brad D.
Abstract : Purpose: Prior research has noted similar functional and subjective outcomes between individuals with delayed amputation vs. limb salvage; however, these reports are generally retrospective in nature. Here, we prospectively compare functional and subjective outcomes from an individual with limb salvage to a delayed transtibial amputation using a single-subject design with sequential participation in a fall-prevention program. Materials and Methods: The subject participated in a fall-prevention rehabilitation training program, once before undergoing a delayed transtibial amputation and again after. As part of the fall-prevention program, the participant completed pretraining and post-training assessments which quantified trunk control by 1) trunk flexion and flexion velocity after trip-inducing perturbations on a treadmill and 2) trunk sway parameters during unstable sitting. In addition, the four square step test was administered, and patient-reported outcomes, including pain, prosthetic/orthotic comfort, and walking/running endurance, were collected. Results: In general, the participant demonstrated improved trunk control after amputation, as evidenced by decreases in trunk flexion and flexion velocity after perturbation and sway parameters during unstable sitting. In addition, four square step test times were shorter with amputation vs. limb salvage; the participant also reported reduced pain and greater comfort with amputation (vs. limb salvage). Conclusions: Although just a single participant, within-subject comparisons provide quantitative evidence that, for some individuals, delayed/late (transtibial) amputation after prolonged limb salvage may be beneficial in reducing pain and restoring function.